Sosialisasi Kesehatan Dampak Positif Pencegahan Penyakit Hiv/Aids Pada Masyarakat Khususnya Terhadap Remaja - Ula, Zumrotul; Harfika, Meiana; Sapnita, Sapnita; Basir, Anastasia A.; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
HIV/AIDS is an incurable disease and requires long-term treatment. Lack of knowledge about the dangers of this disease causes more and more people to be affected, especially in adolescence who often follow the development of the times. The purpose of this community service activity is to increase adolescent knowledge through health socialization of the positive impact of preventing HIV/AIDS in the community, especially in adolescents at SMK students in Surabaya. The method of this service is health socialization about preventing HIV/AIDS in the community, especially in adolescents. The results of this activity showed an increase in broad knowledge among participants from students in grades IX, X and XI consisting of 81 women and 63 men related to HIV/AIDS. The conclusion of the Community Service Activity is that students have a good understanding and have awareness and concern about the importance of preventing and overcoming HIV AIDS.